Short-Course versus Standard-Course Antibiotic Therapy for Pneumonia in Adult: A Systematic Review - Ni Wayan Devi Yulian; I Made Satria Wibawa (Indonesian Health Journal, 2026)
Pneumonia remains a significant cause of morbidity and mortality among adults worldwide, with substantial impacts on healthcare utilization and costs. Despite advancements in vaccines, diagnostics, and antimicrobial therapy, optimizing antibiotic duration remains a clinical challenge. Traditional regimens typically span 7–14 days, but prolonged therapy contributes to antimicrobial resistance, adverse events, and higher healthcare expenses. This study aims to evaluate the effectiveness and safety of short-course (?7 days) versus standard-course (?7 days) antibiotic therapy in adult patients with pneumonia. A systematic review was conducted following PRISMA guidelines, including randomized controlled trials and observational studies published between 2016 and 2026. Data on clinical cure, mortality, recurrence, hospital length of stay, and adverse events were extracted and analyzed. Results from seven studies involving 5,467 patients indicate that short-course therapy is generally non-inferior to standard-course therapy in terms of clinical cure and mortality, particularly among patients achieving early clinical stability. Recurrence rates were comparable, while some studies demonstrated reduced hospital stay and fewer antibiotic-related adverse events in short-course groups. These findings support individualized treatment durations guided by clinical response rather than fixed periods. In conclusion, short-course antibiotic therapy is an effective and safe strategy for appropriately selected adult patients with pneumonia, offering potential benefits for patient outcomes, antimicrobial stewardship, and healthcare resource optimization.